Escolarização e inclusão : narrativas de mães de filhos com Transtorno do Espectro Autista (TEA) - Bassotto, Beatriz Catharina Messinger (My University, 2018)
This dissertation is a qualitative exploratory study of documentary nature, composed of works in Portuguese Language, with authorship of Mothers of children with Autism Spectrum Disorder (ASD). Its objective was to understand the movements of schooling and inclusion in the narratives of mothers of children with Autism Spectrum Disorder (ASD). Seven works of current reading were selected. The construction and analysis of the data of this research were based on the Theory Grounded in the Data, with the aid of the software QSR Nvivo. Two areas of analysis were delimited, namely: Beyond the School Walls and Between the School Walls. The data found in each territory of analysis allowed the creation of five analytical categories named: Family, Society, School, Teachers and Legislation. The results of the analysis indicated a strong correlation between Maternity and family relationships in the daily life, considering the impact of the diagnosis and feelings of guilt and mother acceptance. The relation between family and school still appears distant, in the narratives of the mothers. Family relations, especially the mother‟s with health professionals deserve attention, as they can directly influence the referrals needed for children with ASD, starting with socializing. In the school environment, the lack of information and the fear of the unknown are attitudinal barriers, which interfere in teaching, even with the didactic and pedagogical resources available. The study also demonstrated the importance of integrated work in schools, involving teachers, health professionals and families, articulating the knowledge of different areas. The legislation is configured as a support for the actions initiated in the school to extend to society. The study suggests possibilities for continuity, exploring in depth each analytical category of this research, correlating with social, academic, political and school contexts.
A presente dissertação constitui-se em um estudo qualitativo exploratório de caráter documental, composto de obras em Língua Portuguesa, com autoria de Mães de filhos com Transtorno do Espectro Autista (TEA). O objetivo foi compreender os movimentos de escolarização e inclusão nas narrativas de mães de filhos com Transtorno do Espectro Autista (TEA). Foram selecionadas sete obras de leitura corrente. A construção e a análise dos dados desta pesquisa foram baseados na Teoria Fundamentada nos Dados, com auxílio do software QSR Nvivo. Foram delimitados dois territórios de análise, a saber: Além dos Muros da Escola e Entre os Muros da Escola. Os dados encontrados em cada território de análise possibilitaram a criação de cinco categorias analíticas nomeadas de: Família, Sociedade, Escola, Professores e Legislação. Os resultados da análise indicaram uma forte correlação entre a Maternidade e as relações familiares no cotidiano, tendo em vista o impacto do diagnóstico e os sentimentos de culpa e aceitação da mãe. A relação entre família e escola ainda aparece distante, nas narrativas das mães. As relações da família, em especial a mãe, com os profissionais da saúde, merecem atenção, pois podem influenciar diretamente os encaminhamentos necessários às crianças com TEA, iniciando pelo convívio em sociedade. No ambiente escolar, a falta de informação e o medo do desconhecido configuram-se em barreiras atitudinais, que interferem no fazer docente, mesmo com os recursos didáticos e pedagógicos disponíveis. O estudo demonstrou também a importância do trabalho integrado nas escolas, envolvendo professores, profissionais da saúde e as famílias, articulando os saberes de diversas áreas. A legislação configura-se como um suporte para que as ações iniciadas na escola se estendam para a sociedade. O estudo sugere possibilidades de continuidade, explorando em profundidade cada categoria analítica desta pesquisa, correlacionando com os contextos sociais, acadêmicos, políticos e escolares.
Keywords: Autismo; Inclusão escolar; Educação inclusiva; Autism; Mainstreaming in education; Inclusive education